Learning Implementation Improves Students' Thinking Skills - Nainggolan, Assyifa Nahdhah (International Journal of Students Education, 2025)
This research examines the application of the Problem Based Learning (PBL) model in improving students' critical thinking skills in the 21st century learning era. Using the systematic literature review (SLR) method with a qualitative approach, this research analyzes various literature from the Google Scholar database to synthesize related findings. effectiveness of PBL in developing critical thinking skills. The research results show that PBL is an effective learning model in improving students' critical thinking skills through real problem-based learning. This model encourages students to be active in finding solutions, gathering relevant information, and developing analytical skills. The teacher's role as a facilitator is very important in guiding students through the stages of PBL learning, from problem orientation to evaluation. This research also identifies challenges in implementing PBL and strategies to overcome them. Effective implementation of PBL can contribute to the development of essential critical thinking skills for students in facing the challenges of the 21st century.